Implementation of Kangaroo Mother Care (KMC) for low birth weight babies (LBWBs) at Budi Kemuliaan Mother and Child Hospital: a qualitative study - Rahmayanti Rahmayanti; Hadi Pratomo; Ulfi Hida Zainita; Myranti Myranti (Indonesian Journal of Perinatology, 2021)
Introduction: The infant mortality rate is one indicator of the public health quality in a country. One of the main causes of infant mortality is low birth weight babies (LBWBs). Kangaroo Mother Care (KMC) is a treatment method for LBWBs by making direct contact between the baby’s skin and the mother’s skin. Budi Kemuliaan Mother and Child Hospital already practicing KMC since 2010 and it has succeeded. The purpose of this study was to determine the implementation of KMC for LBW mothers at Budi Kemuliaan Mother and Child Hospital. Methods: This study was qualitative research with Rapid Assessment Procedures (RAP) design. This research was conducted on mothers who gave birth with LBWB (<2500 grams) from 9 to 18 December 2011, and practice KMC at Budi Kemuliaan Mother and Child Hospital, Jakarta. Result: The implementation of KMC for LBW mothers at Budi Kemuliaan Mother and Child Hospital was affected by seven factors. Those factors were; mothers and their husbands have sufficient knowledge of KMC from health workers explanation, good acceptance attitude, given accountable information sources of KMC, there is the presence of KMC policy that supporting KMC program, health workers support, husband support, and sufficient health education and counseling of KMC for mother and their husband before discharge. Conclusion: There are seven factors that determine the successful implementation of KMC for LBW mothers at Budi Kemuliaan Mother and Child Hospital, those are; sufficient knowledge of KMC, acceptance attitude of KMC, information sources of KMC, the presence of KMC policy, health workers support, husband support, and sufficient health education of KMC for mother before discharge. This study suggested the formation of a support group to build social support between LBW families.